1991
DOI: 10.1016/0014-5793(91)80882-4
|View full text |Cite
|
Sign up to set email alerts
|

A model for fd phage penetration and assembly

Abstract: Below 15°C, chloroform causes fd phage to contract to I‐forms, which are compact structures about 1/3 as long as the original phage. Above 15°C, chloroform causes I‐forms to contract to even more compact spheroidal S‐forms. Here we show that the coat protein structure in I‐forms is the same as the protein structure in the phage and the protein structure in S‐forms is the same as the protein structure in bilayers. The conversions from fda˚I‐forms→S‐forms are ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The peculiarities of this process were analyzed in detail for the fd phage penetrating host cells. 195,196 Here, fd phage was shown to undergo large morphological changes, morphing first from the highly extended original form to the contracted I-form, about 1/3 as long as the original phage, then to the micelle-like spherical S-form, and finally to a helical form embedded in membrane bilayers. 196 Detailed biophysical analysis revealed that both I- and S-forms of the fd phage represented compact conformations characterized by nonrigid side chain packing and non-native morphologies but native-like secondary structures.…”
Section: Active Factors Promoting Transient Disorder: Interaction-mentioning
confidence: 98%
“…The peculiarities of this process were analyzed in detail for the fd phage penetrating host cells. 195,196 Here, fd phage was shown to undergo large morphological changes, morphing first from the highly extended original form to the contracted I-form, about 1/3 as long as the original phage, then to the micelle-like spherical S-form, and finally to a helical form embedded in membrane bilayers. 196 Detailed biophysical analysis revealed that both I- and S-forms of the fd phage represented compact conformations characterized by nonrigid side chain packing and non-native morphologies but native-like secondary structures.…”
Section: Active Factors Promoting Transient Disorder: Interaction-mentioning
confidence: 98%